Development of the Beliefs in Human Nature Uniqueness Scale and Its Associations With Perception of Social Robots - Jean-Christophe Giger; Nuno Piçarra; Grzegorz Pochwatko; Nuno Almeida; Ana Susana Almeida; Neuza Costa (Human Behavior and Emerging Technologies)
Isaac Asimov (1982) in Foundation’s Edge, p. 420